Advances in the propagation of Brazilian Cherry tree - Alberto da Silva, Jose Antonio; Almeida Teixeira, Gustavo Henrique de [UNESP]; Citadin, Idemir; Wagner Junior, Americo; Danner, Moeses Andrigo; Geraldo Martins, Antonio Baldo [UNESP] (Soc Brasileira Fruticultura, 2019)
Brazilian Cherry tree is a native fruit tree belonging to the Myrtaceae family, with ample adaptation to the different edaphoclimatic conditions of Brazil, which makes this fruit widely known. However, there are still few commercial orchards, which may soon be reversed, since studies have shown the benefits of the consumption of this fruit for human health, as well as the potentialities for industrial processing. Thus, Brazilian Cherry tree will no longer be a backyard plant and will be grown in commercial orchards, which demands the production of seedlings with genetic quality. Sexual propagation with the use of seeds should be replaced by asexual propagation by means of cutting, grafting, spreading and tissue culture. The grafting method has proven to be efficient in more than 70% of cases and herbaceous cuttings have rooting greater than 77%. New studies on micropropagation and better control of herbaceous cutting processes should stimulate and economically increase the commercial production of this fruit for fresh consumption or processing. This review article included the results of other studies, addressing advances, limitations and protocols for propagation of Brazilian Cherry tree.
Keywords: Brazilian Cherry; Myrtaceae; seeds; Surinan Cherry; propagation techniques